Validation of test setup to evaluate glide performance in skis - Swaren, M.; Karlöf, L; Holmberg, H. C.; Eriksson, A. (Sports Technology, 2014)
Although today's ski waxing chemicals and micro-machining techniques of the ski base are highly sophisticated, objective procedures for testing and verification of the results have not yet been developed and evaluation is based on comparison of subjective experience. The purpose of the present study was thus to compare different setups for testing the glide of cross-country skis. Two differently waxed ski pairs were tested for glide inside a ski tunnel. Inertial measurement units (IMUs) were attached to each ski; instantaneous velocities monitored by three different speed-traps; the velocities during the acceleration phase determined by Doppler radar. Kinetic, potential and total energy, giving the energy dissipation, were calculated for four representative trials during the acceleration phase. No reliable data were obtained from the IMUs due to high drift. The mean maximal velocity for the two ski pairs were 6.97, s = 0.09 and 6.70, s = 0.09 m/s, respectively. Higher differences between the skis were identified during the retardation phase compared to the acceleration phase. The mean difference between the velocities determined by the speed-trap and Doppler radar was 0.6, s = 1%, demonstrating that the latter provides accurate data for evaluation of gliding characteristics and performance. However, theoretical confirmation of the friction coefficient, on the basis of data provided by Doppler radar and energy calculations requires exact measurements of the inclination and topography of the track in question.